2000
DOI: 10.1046/j.1469-8137.2000.00587.x
|View full text |Cite|
|
Sign up to set email alerts
|

Tansley Review No. 110.

Abstract: Orchid seeds are very small, extremely light and produced in great numbers. Most range in length from c. 0.05 to 6.0 mm, with the difference between the longest and shortest known seeds in the family being 120-fold. The ' widest ' seed at 0.9 mm is 90-fold wider than the ' thinnest ' one, which measures 0.01 mm (because orchid seeds are tubular or balloon-like, ' wide ' and ' thin ' actually refer to diameter). Known seed weights extend from 0.31 µg to 24 µg (a 78-fold difference). Recorded numbers of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(143 citation statements)
references
References 61 publications
4
108
0
4
Order By: Relevance
“…The variable properties of seeds (shape, weight, proportion of air space) are among the causes of differentiated distances of seed dispersal in orchid species [38]. For example, Arditti and Ghani [38], Shimizu et al [58], and Kiyoharaet et al [59] found different seed velocities according to certain properties, such as weight or proportion of air space. Seeds with large air spaces drop more slowly, and therefore will have a lower settling velocity.…”
Section: Factors Influencing Seed Dispersal In Orchidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variable properties of seeds (shape, weight, proportion of air space) are among the causes of differentiated distances of seed dispersal in orchid species [38]. For example, Arditti and Ghani [38], Shimizu et al [58], and Kiyoharaet et al [59] found different seed velocities according to certain properties, such as weight or proportion of air space. Seeds with large air spaces drop more slowly, and therefore will have a lower settling velocity.…”
Section: Factors Influencing Seed Dispersal In Orchidsmentioning
confidence: 99%
“…The lack of such information for one of the most endangered plant families is an important deficiency, because this parameter influences the persistence, dynamics, and evolution of orchid populations. Orchid seeds are generally assumed to be widely dispersed by wind because of their small size and low weight, in addition to their embryos occupying only a very small percentage of the space inside the testae (with an air content from 60 to above 90%) [36][37][38]. According to Gandawijaja and Arditti [39], these characteristics enabled orchids to reach Krakatau from Java (distance ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 The mature orchid seed is "dustlike" in size and weight, lacks a primordial shoot/root axis, and the protoderm is the only distinctive primary meristem. [46][47][48] Upon germination, embryo cells divide to form a protocorm, which is a tuberous, sphere or oblong structure that is several times the dimensions of the original embryo, and comprised of undifferentiated cells. 45,[49][50][51] Approximately two to three weeks later, a meristem forms with evidence of a first leaf.…”
Section: Polar Auxin Transport Affects Protocorm and Meristem Formationmentioning
confidence: 99%
“…As orquídeas possuem limitações que dificultam a germinação de sementes como, por exemplo, a espessura da parede das células do tegumento envoltório do embrião e a quantidade de endosperma presente no embrião que, muitas vezes, é insuficiente para a germinação (Arditti & Ghani 2000). As plântulas de orquídeas podem ser obtidas, em laboratório, tanto por germinação assimbiótica in vitro, utilizando meios de cultivo assépticos (Hossain et al 2010;Favetta et al 2014), quanto germinação simbiótica com fungos micorrízicos (Zettlet et al 2007) ou, ainda, micorrização de plântulas provenientes de germinação assimbiótica (Wu et al 2011).…”
unclassified